Performance and mechanism of Carrousel oxidation ditch and water Spinach wetland combined process in treating water hyacinth (Pontederia crassipes) biogas slurry - Yaqin Yu; Xueyou Fang; Lanying Li; Yumeng Xu (Archives of Environmental Protection, 2023)
Owing to its high concentrations of nitrogen and phosphorus, the slurry from water hyacinth (Pontederia crassipes) biogas production cannot be discharged directly without further treatment. To achieve the target of water recycling, a new strategy of combining a Carrousel oxidation ditch with a water spinach wetland was developed in this study for the harmless treatment of Pontederia crassipes biogas slurry. First, the water quality characteristics of the biogas slurry were measured. Then, comprehensive tests of the combined slurry treatment system were carried out to verify pollutant removal performance and mechanism. The results showed that the Carrousel oxidation ditch reduced the inlet pollutant load of the subsequent water spinach wetland. The chemical oxygen demand (COD), and ammonium nitrogen (NH4+-N), total nitrogen (TN), and total phosphorus (TP) contents of the average effluent from the combined system were less than 50 mg/L, 1.6 mg/L, 6 mg/L, and 0.5 mg/L, respectively, which means that all met urban sewage treatment standard of Level 1 Grade A (GB18918-2002). Gas chromatography – mass spectrometry analysis showed that the combined system had decreased various types of organic pollutants in the biogas slurry exponentially, efficiently removing alkane pollutants, aromatic hydrocarbons, and heterocyclic compounds. Scanning electron microscopy images revealed very large surface area of the water spinach roots in the wetland, which played important roles in enriching the microorganisms and trapping organic matter. Plant absorption, microbial degradation, and filtration were the primary ways in which the water spinach wetland purified the biogas slurry.